Use of lectin as a vector molecule for delivery of medicinal products to cells and tissues - Antonyuk, V.O.; Klyuchivska, O.Yu.; Antonyuk, R.V.; Lozynskyi, A.V.; Pohranychna, Kh.R.; Lesyk, R.B.; Stoika, R.S. (Вiopolymers and Cell, 2016)
Aim. The conjugation of low-molecular compounds with antitumor activity to lectin and evaluation of the biological activity of the obtained conjugate. Methods. Organic synthesis; obtaining and analyzing Pisum sativum agglutinin with thiopyrano[2,3-d]thiazole derivative conjugate; its biological testing on cell cultures and histological samples. Results. A conjugate of the Pisum sativum lectin with the thiopyrano[2,3-d]thiazole derivative was obtained. Conjugation was carried out through the interaction of the aldehyde groups with the amino groups of lectin in the alkaline medium (pH 9.0). The compound (0.4 mg) was immobilized on lectin (10 mg). Conjugation of pea lectin with the antineoplastic agent led to a ~ 2.5-fold increase in the inhibitory effect tested on a L1210 mouse leukemia cells line. The antineoplastic effect of the studied conjugate is fully manifested only on the third day after the beginning of experiment, possibly after penetration of the conjugate into cells and its desintegration. Conclusions. The results may be used for development of new drug delivery systems. Мета. Приєднання низькомолекулярної сполуки з протипухлинною активністю до лектину та визначення біологічної активності одержаного кон’юґату. Методи. Органічний синтез; одержання та аналіз кон’юґату лектину гороху з похідним тіопірано[2,3-d]тіазолу, біотестування кон’югату на культурі клітин та гістологічних препаратах. Результати. Одержано кон’югат лектину гороху (Pisum sativum) приєднаним похідним тіопірано[2,3-d]тіазолу. Кон’югацію здійснювали через взаємодію альдегідної групи сполуки похідного з аміногрупами білка лектину в лужному середовищі (рН 9,0). До 10 мг лектину було приєднано ≈ 0,4 мг досліджуваної сполуки. Кон’юґація лектину гороху з протипухлинною речовиною спричинила підсилення інгібувальної дії останньої на клітини лінії L1210 лейкозу миші приблизно у 2,5 рази (у перерахунку на речовину). Антинеопластична дія кон’югату в повній мірі проявляється лише на третю добу від початку досліду, й імовірно після проникнення кон’юґату у кліти-ну і розпаду молекули. На гістологічному препараті визначено особливості зв’язування досліджуваного кон’югату з мукозними клітинами прямої кишки людини. Висновки. Одержані результати можуть бути цікавими для моделювання адресної доставки біологічно активних речовин в клітини тканин організму. Цель. присоединение низкомолекулярного соединения с противоопухолевой активностью к лектину и проверка биологической активности полученного конъюгата. Методы. Органический синтез; получение и анализ конъюгата лектина гороха с производ-ным тиопирано[2,3-d]тиазола, биотестирование конъюгата на культуре клеток и гистологических препаратах. Результаты. По-лучен конъюгат лектина гороха (Pisum sativum) с присоединенным производным тиопирано[2,3-d]тиазола. Конъюгацию осуще-ствляли через взаимодействие альдегидной группы соединения производного с аминогруппами белка лектина в щелочной среде (рН 9,0). К 10 мг лектина было присоединено ≈ 0,4 мг исследуемого соединения. Конъюгация лектина гороха с противоопухоле-вым веществом вызвала усиление ингибирующего действия вещества на клетки линии L1210 лейкоза мыши примерно в 2,5 раза (в пересчете на вещество). Антинеопластическое действие конъюгата в полной мере проявляется лишь на третьи сутки от нача-ла опыта, и вероятно после проникновения конъюгата в клетку и распада молекулы. На гистологическом препарате определены особенности связывания исследуемого конъюгата с мукозными клетками прямой кишки человека Выводы. Полученные резульаты представляют интерес для моделирования адресной доставки биологически активных веществ в клетки тканей организма.